Analisis Defect Rajungan (Portunus pelagicus) Kaleng Menggunakan Metode Failure Mode And Effect Analysis (FMEA) Di PT. XYZ - Hasibuan, Nirmala Efri; Basri, Basri; Ratrinia, Putri Wening; Suryono, Muh; Azka, Aulia; Saputra, Eko Novi; Meutia, Meta (Jambura Fish Processing Journal, 2024)
PT XYZ  is an industry that operates in the fisheries sector with superior products, pasteurized crab meat in cans. Increasing market demand, including demand for canned crab exports, requires companies to produce products quickly and correctly. However, in the production of canned crab, defective products are often found or do not meet quality standards. The aim of this research is to identify defect problems in canned crab products and provide suggestions for improvements to overcome the problem in order to minimize the occurrence of defects that are detrimental to the company. Research data collection methods are through observation, interviews and questionary. The Failure Mode and Effect Analysis (FMEA) method is used to identify and analyze defects that occur. FMEA is used to determine the severity level, occurrence level and detection level, so that a Risk Priority Number (RPN) value can be obtained which can determine the priority of defects that must be prioritized for repair. The identification results at PT XYZ found 7 types of defects. The highest RPN defect value that occurs is a rust defect with an RPN value of 324. The defects that occur in this problem are caused by 4 factors, namely humans, methods, materials and the environment. Proposed improvements to reduce the chance of defects occurring in cans include material inspection, human/operator error evaluation, maintaining process environmental conditions, and optimizing the implementation of standard operating procedures (SOP)